The Role of Liquid Organic Fertiliser on the Growth of Rice Paddy Crops in Pape Village, Bajawa District, Ngada Regency, East Nusa Tenggara Province - Lea, Victoria Coo; Prihatin, Prihatin; Hamakonda, Umbu Awang; Puspita, Victoria Ayu; Taus, Igniosa; Due, Maria Serviana (Jurnal Biologi Tropis, 2024)
The production and growth of Oryza sativa L. rice plants are crucial for maintaining the long-term viability of food agriculture. The purpose of this study was to assess how liquid organic fertilizer affected the growth of the rice cultivars Kusuma 06 and Inpari 30. The study was carried out in Pape Village, which is situated in Bajawa Sub-district, Ngada Regency, East Nusa Tenggara Province, from January to April of 2024. The research method involved the application of liquid organic fertiliser to Inpari 30 and Kusuma 06 rice plants in the field during the research period. The height, number of leaves, and number of tillers on rice plants were noted, as well as the infestation rate of false whiteflies and brown stem leafhoppers. The results demonstrated that liquid organic fertiliser exerted a significant influence on rice plant growth, with enhanced plant height, leaf number, and tiller number observed in plants treated with liquid organic fertiliser. Furthermore, the infestation of false white pests and brown stem leafhoppers also exerted a notable impact on the growth and yield of rice plants, resulting in a reduction in grain production and substantial economic losses. The results of research conducted in Pape Village, Bajawa District, Ngada Regency indicated that the Inpari 30 rice variety yielded 9 sacks, while the Kusuma 06 variety yielded 7 sacks. The productivity of the Inpari 30 rice variety was found to be superior, particularly among wetland rice farmers. Consequently, the application of liquid organic fertiliser and integrated pest control is crucial to the practice of paddy rice farming in order to achieve optimal yields.